Motif Belajar Pada Siswa Suku Anak Dalam (SAD) di SMK Negeri 1 Merangin Provinsi Jambi - Indri Fitriani; Nelyahardi Nelyahardi; Siti Amanah (Departement of Mathematics Education, 2023)
This research held on MA Al-Mawaddah, a school that uses boarding school with pesantren type as the system. This research aims to determine the effect of boarding school on Economic learning achievement of MA Al-Mawaddah students. The research classified as ex-post facto with quantitative method. The population was all students from social major class X, XI, and XII with total 202 students. The sample was taken using probability sampling and the sample technique was proportionate random sampling, and the total sample was 134 students. Data collection technique for Economic learning achievement used documentation and questionaries for boarding school. The instrument tested by validity and reliability test. The validity test used Pearson Product Moment and the reliability test used Cronbach Alpha. The hypothesis tested with linear regression test. The results show that boarding school has positive and significant effect on Economic learning achievement, it showed with t-test result (tcount >ttable, 4,799 > 1,97824). The amount of boarding school effect towards Economic achievement is 14,9%.